2016
DOI: 10.1080/02678292.2016.1197429
|View full text |Cite
|
Sign up to set email alerts
|

Graphene and liquid crystal mediated interactions

Abstract: The two-dimensional graphene-honeycomb structure can interact with the liquid crystal's (LC) benzene rings through π-π electron stacking. This LC-graphene interaction gives rise to a number of interesting physical and optical phenomena in the LC. In this paper, we present a combination of a review and original research of the exploration of novel themes of LC ordering at the nanoscale graphene surface and its macroscopic effects on the LC's nematic and smectic phases. We show that monolayer graphene films impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 55 publications
(71 reference statements)
0
39
1
Order By: Relevance
“…It has been experimentally demonstrated that due to this nano-architectural symmetry of the hexagons in both the species, the benzene rings of the LC coherently align on the hexagonal lattice of h-BN [18]. The interactions between the nematic LC and the hexagonal lattice of other different nanomaterials (e.g., graphene, carbon nanotube, molybdenum diselenide, tungsten diselenide) [19][20][21][22][23][24][25][26][27][28][29] have also demonstrated that the LC can achieve a planar-aligned state on the hexagonal nanosurface. The density functional calculations showed that this planar anchoring of the LC on the hexagonal nanostructure is further strengthened with a binding energy, ranging from 0.7 to 2.0 eV/molecule [21,27,39], by the electrostatic energy resulting from a considerable amount of charge transfer between the LC molecules and the hexagonal lattice structure.…”
Section: Fabrication Of the Electro-optic Lc Cell Employing 2d H-bn Amentioning
confidence: 99%
“…It has been experimentally demonstrated that due to this nano-architectural symmetry of the hexagons in both the species, the benzene rings of the LC coherently align on the hexagonal lattice of h-BN [18]. The interactions between the nematic LC and the hexagonal lattice of other different nanomaterials (e.g., graphene, carbon nanotube, molybdenum diselenide, tungsten diselenide) [19][20][21][22][23][24][25][26][27][28][29] have also demonstrated that the LC can achieve a planar-aligned state on the hexagonal nanosurface. The density functional calculations showed that this planar anchoring of the LC on the hexagonal nanostructure is further strengthened with a binding energy, ranging from 0.7 to 2.0 eV/molecule [21,27,39], by the electrostatic energy resulting from a considerable amount of charge transfer between the LC molecules and the hexagonal lattice structure.…”
Section: Fabrication Of the Electro-optic Lc Cell Employing 2d H-bn Amentioning
confidence: 99%
“…On the honeycomb -like hexagonal pattern, the LC molecules can form short-range order due to ππ stacking, by matching the LC's benzene rings on the honeycomb structure. [32][33][34][35][36][37] See Fig. 1(b).…”
Section: Experiments Results and Discussionmentioning
confidence: 99%
“…The diminished presence of free-ions can reduce the internal friction, resulting in a decrease in the rotational viscosity γ 1 , of the LC media. [29][30][31]34,35 A reduction in γ 1 , therefore, causes a faster rotation of the LC molecules. It is possible that NDs, being a carbon allotrope, also trap some ions and reduce the free-ion concentration in LC, decreasing γ 1 -hence the observed accelerated responses for τ on and τ off in the E7+ND sample.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoscale interactions between nematic liquid crystals (LCs) and various two-dimensional (2D) hexagonal nanomaterials show interesting phenomena at the macroscopic levels. For example, the epitaxial interactions between the nematic LC and the hexagonal lattice of graphene, molybdenum diselenide, and tungsten diselenide deposited [1][2][3][4][5][6][7][8][9][10] demonstrate that the LC can achieve a planar-aligned state on these 2D hexagonal nanostructures. Our group has recently shown that the 2D hexagonal boron nitride (h-BN) film can be successfully employed as a planar-alignment agent as well as an ion-capturing agent in electro-optic LC devices [11][12][13].…”
Section: Introductionmentioning
confidence: 99%